One-Pot Synthesis of Nucleoside 5′-Triphosphates from Nucleoside 5′-H-Phosphonates - Sun, Qi (2008)
[Image: see text] Nucleoside 5′-triphosphates (NTPs) play key roles in biology and medicine. However, these compounds are notoriously difficult to synthesize. We describe a one-pot method to prepare NTPs from nucleoside 5′-H-phosphonate monoesters via pyridinium phosphoramidates, and we used this approach to synthesize ATP, UTP, GTP, CTP, ribavirin-TP, and 6-methylpurine ribonucleoside-TP (6MePTP). Poliovirus RNA-dependent RNA polymerase efficiently employed 6MePTP as a substrate, suggesting that the cognate nucleoside, a poorly understood antiviral agent, may damage viral RNA.